Electric vehicles market outlook - Potential consumers, information services and sites test - Zulkarnain; Leviakangas, Pekka; Tarkiainen, M.; Kivento, T. (Universitas Indonesia, 2012)
The purpose of this paper is to review the most recent and relevant business intelligence and market foresight analyses on electric vehicles in order to build a picture on the current market activities and offerings. The reference material was clustered in three main sources: 1) market foresight analyses 2) information services development activities, 3) probe of electric vehicle test sites. The future EV market is seen to have a promising growth potential, though the proper business models that could meet consumer aspirations are still called for. The growing potential of EV market has been stimulating the development of several types of services that support EV deployment, e.g. information services. The test sites are already emerging around the globe and the master driver seems to be the automotive industry. © IJTech 2012.